Beyond the brain : how body and environment shape animal and human minds - Barrett, Louise (Princeton, N.J : Princeton University Press, 2011)
Drawing on examples from animal behavior, comparative psychology, robotics, artificial life, developmental psychology, and cognitive science, this title provides fresh insights into how animals and humans depend on their bodies and environment - not just their brains - to behave intelligently.
Includes bibliographical references and index
NUR
Keywords: Brain -- Evolution; Evolution (Biology); Ecology; Cognition -- Physiology; Biological evolution; Brain -- Physiology